International Accounting - Le, Thi Mai (Khoa Quốc tế, ĐHQGHN, 2020)
This course aims to prepare students with the diversity of accounting practices around the world. Main learning areas are Accounting issues that are faced by multinational organizations. Students will be provided understanding how accounting is practiced under differences and changes and how to deal with specific accounting issues in international business environments. The course also focuses in the diversity of accounting standards and practices in selected countries.